Life is war surviving dictatorship in communist Albania - Woodcock, Shannon (HammerOn Press, 2016)
Life is War: Surviving Dictatorship in Communist Albania is a collection of oral histories that guides readers through through the decades (1944-1992) in which everything was controlled by the Communist Party; what work one could do, what food was available, and even who one could marry.